A multi-scale model analysis of ozone formation in the Bangkok Metropolitan Region, Thailand. (15th May 2020) - Uttamang, Pornpan; Campbell, Patrick C.; Aneja, Viney P.; Hanna, Adel F.
Abstract: Over the last three decades, Thailand's rapid industrialization and urbanization have led to an impact on urban air quality. A majority of the country's development has occurred within and around Bangkok (BKK), the capital city of Thailand, and the Bangkok Metropolitan Region (BMR). Since 1995, the BMR has experienced air quality degradation, in particular, enhanced ozone (O3 ) due to a combination of the local increase in emissions from accelerated growth in automotive and industrial activities, local meteorology including strong solar radiation, high temperature and high humidity, and potential long-range effects of regional transport from China. To investigate the O3 formation in the BMR due to the effects of long-range transport and local meteorology feedbacks, we perform a multi-scale simulation with the Weather Research and Forecasting model with Chemistry (WRF-Chem) during the O3 season (January to March), 2010; since O3 mixing ratio exceedances in the BMR occur primarily during this period The results in this study indicate the significance of China's emission reductions on the regional-scale and the local-scale pollution, as far as the BMR region and southern Thailand. Applying China's oxide of nitrogen (NOx )-only emission controls, generally, enhance the domain-wide monthly-average peroxyacetyl nitrate (PAN) and O3 in the regional scale, in the order of 1–7% and 1–5%, respectively, while those in the local scale are 0.2–6% and 0.1–5% compared with the baseline simulation. However, the increases in PAN and O3 are mitigated by 40% China's Volatile Organic Compound (VOC) reduction along with 40% NOx reduction. The results, supported by an indicator analysis, suggest that northern and eastern China, northern and central Thailand and the BMR, are likely VOC-limited during the O3 season. Since the BMR is VOC-limited regime, controlling anthropogenic VOC emissions will show more benefit to control O3 than controlling NOx -only emissions. Other factors that influence on O3 levels in the BMR are biogenic VOC emissions from the Tenasserim range and land- and sea-breeze circulations that recirculate and disperse pollutants along the coastal areas. Graphical abstract: Image 1 Highlights: Ozone nonattainment in the Bangkok Metropolitan Region. WRF-Chem modeling analysis. Long-range transport of pollutants. Impact of China's emission in the Bangkok Metropolitan Region. Sensitivity of NOx and VOC emissions.